Contribution of incentives towards establishment of local brand name to international market / Siti Rohimah Yusoff - Yusoff, Siti Rohimah (2010)
Grant can be define as an award of financial assistance in the form of money by the federal government to an eligible grantee with no expectation that the funds will be paid back. The term does not include technical assistance which provides services instead of money, or other assistance in the form of revenue sharing, loans, loan guarantees, interest subsidies, insurance, or direct appropriations. Grant normally related to SME and Non SME Sectors as it help both sectors with financial assistant, business motivation, business encouragement, and much more. This paper empirically analysed the contribution on how this grant can help SME and Non-SME to the establishment of local brand name to international market, the amount that had been given to SME and Non-SME and also to know the difficulties facing by these companies in following the guidelines. The study will use secondary data gathered form many sources such as interview session, data from organization. This paper also will reveal what are the reasons by MATRADE in providing this grants and why it is given differently to both SME and Non-SME companies.